Emerging nanomaterials applied for tackling the COVID-19 cytokine storm. Issue 39 (16th September 2021) - Yang, Xi; You, Jia; Wei, Yuanfeng; Li, Huawei; Gao, Ling; Guo, Qing; Huang, Ying; Gong, Changyang; Yi, Cheng
Abstract : Emerging nanomaterials applied for tackling the COVID-19-associated cytokine storm. Cur-SLNs, curcumin-loaded solid lipid nanoparticles; 25-HC, 25-hydroxycholesterol. Abstract : During the global outbreak of coronavirus disease 2019 (COVID-19), a hyperinflammatory state called the cytokine storm was recognized as a major contributor to multiple organ failure and mortality. However, to date, the diagnosis and treatment of the cytokine storm remain major challenges for the clinical prognosis of COVID-19. In this review, we outline various nanomaterial-based strategies for preventing the COVID-19 cytokine storm. We highlight the contribution of nanomaterials to directly inhibit cytokine release. We then discuss how nanomaterials can be used to deliver anti-inflammatory drugs to calm the cytokine storm. Nanomaterials also play crucial roles in diagnostics. Nanomaterial-based biosensors with improved sensitivity and specificity can be used to detect cytokines. In summary, emerging nanomaterials offer platforms and tools for the detection and treatment of the COVID-19 cytokine storm and future pandemic.